1999
DOI: 10.1161/01.atv.19.3.598
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alcohol and Cholesterol Feeding on Lipoprotein Metabolism and Cholesterol Absorption in Rabbits

Abstract: Abstract-Alcohol fed to rabbits in a liquid formula at 30% of calories increased plasma cholesterol by 36% in the absence of dietary cholesterol and by 40% in the presence of a 0.5% cholesterol diet. The increase was caused almost entirely by VLDL, IDL, and LDL. Cholesterol feeding decreased the fractional catabolic rate for VLDL and LDL apoprotein by 80% and 57%, respectively, and increased the production rate of VLDL and LDL apoprotein by 75% and 15%, respectively. Alcohol feeding had no effect on VLDL apopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Already, the triglycerides levels were significant for the [GRF2] group, decreasing by 36% in relation to the control (p<0.05) and increasing levels in [ALC2] compared to [GRF2] (p<0.05). The increase in cholesterol levels at 13.98 mg.dL -1 in the [ALC1] group may reflect the increased absorption of dietary cholesterol or the induction of cholesterol absorption by alcohol (Latour et al, 1999). These findings were consistent with previous studies indicating that alcohol affected lipid metabolism (Toffolo et al, 2012) with increased cholesterol levels in rats treated with alcohol (Silva et al, 2015).…”
Section: Resultssupporting
confidence: 90%
“…Already, the triglycerides levels were significant for the [GRF2] group, decreasing by 36% in relation to the control (p<0.05) and increasing levels in [ALC2] compared to [GRF2] (p<0.05). The increase in cholesterol levels at 13.98 mg.dL -1 in the [ALC1] group may reflect the increased absorption of dietary cholesterol or the induction of cholesterol absorption by alcohol (Latour et al, 1999). These findings were consistent with previous studies indicating that alcohol affected lipid metabolism (Toffolo et al, 2012) with increased cholesterol levels in rats treated with alcohol (Silva et al, 2015).…”
Section: Resultssupporting
confidence: 90%
“…Component changes within lipoproteins (e.g., addition or depletion of CE or TG) may indicate poor assembly or removal [19]. As shown in the current study, VLDL particles were altered in terms of components, i.e., lower CE:PRO and TG:PRO ratios for ducklings originating from 24-week-old breeders.…”
Section: Discussionsupporting
confidence: 60%
“…The increase of cholesterol levels by approximately 20 mg¡dL −1 in the [EP10] and [Alc10] groups may reflect increased absorption of dietary cholesterol or altered protein metabolism. Some authors have reported a relationship between alcohol and both increased cholesterol levels and protein metabolism; this reflects channeling of peripheral amino acids to hepatic protein synthesis [ 25 ] and induction of cholesterol uptake [ 26 ] by alcohol. The mechanisms involved in the reduction of cholesterol levels by pterocarpans include acyl-CoA cholesterol acyltransferase (ACAT) inhibition.…”
Section: Discussionmentioning
confidence: 99%